2006
DOI: 10.1128/jvi.02501-05
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Origin of Membrane Vesicles Associated with the Severe Acute Respiratory Syndrome Coronavirus Replication Complex

Abstract: The RNA replication complexes of mammalian positive-stranded RNA viruses are generally associated with (modified) intracellular membranes, a feature thought to be important for creating an environment suitable for viral RNA synthesis, recruitment of host components, and possibly evasion of host defense mechanisms. Here, using a panel of replicase-specific antisera, we have analyzed the earlier stages of severe acute respiratory syndrome coronavirus (SARS-CoV) infection in Vero E6 cells, in particular focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
579
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(616 citation statements)
references
References 72 publications
31
579
1
5
Order By: Relevance
“…We demonstrate here that the replication of a subgenomic replicon of the HCV JFH-1 strain induces numerous 200-500 nm wide DMVs (Fig. 1a-c), similar to those described for poliovirus (Schlegel et al, 1996), severe acute respiratory syndrome (SARS) coronavirus (Snijder et al, 2006) and coxsackievirus B3 (Wong et al, 2008). We also identified some DMVs on EM sections of cells harbouring a subgenomic HCV 1b replicon but in much smaller numbers.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…We demonstrate here that the replication of a subgenomic replicon of the HCV JFH-1 strain induces numerous 200-500 nm wide DMVs (Fig. 1a-c), similar to those described for poliovirus (Schlegel et al, 1996), severe acute respiratory syndrome (SARS) coronavirus (Snijder et al, 2006) and coxsackievirus B3 (Wong et al, 2008). We also identified some DMVs on EM sections of cells harbouring a subgenomic HCV 1b replicon but in much smaller numbers.…”
Section: Discussionmentioning
confidence: 55%
“…In the SARS virus model these virus-induced, ER-derived vesicles seem to have a thick, dense membrane. However, careful EM examination has revealed the presence of double membrane (Snijder et al, 2006), a feature also found in the HCV-induced vesicles. These DMVs were initially thought to carry the SARS virus replication complexes (Snijder et al, 2006) but more recent studies have clearly demonstrated that DMVs contain some non-structural proteins, mostly dsRNA, and that their contents do not appear to be connected to the cytoplasm (Knoops et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus replication in the perinuclear region of the cell is localized to double-membrane vesicles that have been hijacked from the endoplasmic reticulum or late endosomes [37][38][39][40]. These vesicles are around 200-350 nm in diameter and present alone or as clusters in the cytosol [38].…”
Section: Discussionmentioning
confidence: 99%